Predicting Detonation Performance of CHNOFCl and Aluminized Explosives. Issue 5 (26th May 2014) - Keshavarz, Mohammad Hossein; Zamani, Ahmad; Shafiee, Mehdi
Abstract A new "hand‐calculated" method is introduced for prediction of detonation pressure of explosive and mixture of explosives with general formula CHNOFClAl. Suitable decomposition paths are used to estimate heat of detonation and detonation pressure. These decomposition paths are based on the distribution of oxygen atoms between carbon and hydrogen atoms as well as the degree of oxidation of aluminum. For CHNOFCl explosives, it is shown that the predicted detonation pressures with the new method are more reliable with respect to one of the best available empirical methods for loading densities greater than or equal 0.8 g cm−3. Since aluminized explosives have non‐ideal behavior, the new method does not require using full or partial oxidation of aluminum, which is usually required by a computer code. The predicted results of the new model also provide more reliable results than outputs of complex computer code with the BKWS equation of state.